STUDY OF THE PHENOMENON OF MOTHERHOOD WITHIN THE FRAMEWORK OF BEHAVIORIST RESEARCH - Abduvokhobova A. O.; Raimdjanov M. T. (Bright Mind Publishing, 2025)
This article analyzes in detail behavioral studies of the phenomenon of motherhood. It explains on a scientific basis the psychological and social factors that determine the processes of formation, development and manifestation of motherhood. In particular, within the framework of the behavioral approach, the relationship of the mother's behavior with the stimuli of the external environment, its motivational, emotional and behavioral mechanisms in raising children are deeply analyzed. In addition, the article discusses social and biological factors that have a negative impact on motherhood.